Logistik dalam Era Digital: Manajemen Gudang, Kinerja Operasional, dan Perspektif Ekonomi Islam pada PT Sinar Insan Dunia Express, Medan - Gusti Erli Anggi Lubis; Atika; Nurwani (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study examines the impact of operational performance and warehouse management digitalization on logistics productivity at PT Sinar Insan Dunia Express (SIDEX), Medan, through the lens of Islamic economics. Using an associative quantitative design, data were collected via questionnaires from 62 employees across logistics, operations, and warehousing divisions, and analyzed with SPSS version 25 using multiple linear regression. Results indicate that warehouse digitalization significantly enhances logistics productivity and operational efficiency (F(2,59) = 58.65; p < 0.001; Adjusted R2 = 0.654). Specifically, a one-unit increase in digitalization (DG) and operational performance (KO) is associated with a 0.534 and 0.532 increase in productivity (PD), respectively (p < 0.05). Viewed through Islamic economic principles, these practices embody amanah (trust), itqan (work excellence), and maslahah (public benefit), while supporting hifz al-mal (protection of wealth) through accurate records and audit trails. The study underscores the importance for logistics firms to integrate technological innovation with human resource effectiveness under Shariah values to achieve ethical and sustainable business outcomes.